Magma layering of gabbroids of Antarctic Peninsula batholith - G. Artemenko; V. Bakhmutov; I. Samborska; L. Bakhmutova; V. Shpyra (Ukrainian Antarctic Journal, 2013)
The rhythmic layering of coarse-grained gabbroids of late intrusive phase is first detected on the Peterman island. There is similar to the inch layering in well known Stillwater massif. It is caused by alternating bands of gabbroids with varying amounts of pyroxene and ore minerals. In the dark bands of the crystal size of 4×5 mm, and in lightbands - up to 1×2 mm. Following our interpretation the cross-bedding in gabbroids on the contact of melanocratic and light gray gabbroids at Cape Tuxen as a result of crystallization of minerals in the fast flowof magma is proposed. There is important for understanding the formation of layered mafic intrusion and assess the prospects for their ore.